Priority-Based Inter-Vehicle Communication for Highway Safety Messaging Using IEEE 802.11e - Suthaputchakun, Chakkaphong (International Journal of Vehicular Technology, 2009)
We propose to use IEEE 802.11e in conjunction with retransmission mechanisms for priority-based Intervehicle Communication (IVC) for highway safety messaging in both vehicular infrastructure and ad hoc networks. Each IVC message, which is assigned a priority based on the safety event urgency, requires different quality of service in terms of communication reliability and average delay. To increase the communication reliability in a broadcast-based IVC, we apply retransmission mechanisms that can provide proportional reliability differentiation for each prioritized message. We evaluate the performance of our proposed protocol using OPNET Modeler, in terms of percentage of successful transmissions and average delay. The protocol performance is evaluated for (1) different system parameters such as the packet size, number of vehicles, and percentage of priority 1 vehicles, and (2) priority-based protocol parameters, such as contention window, interframe spacing and retransmission parameters. The results show that proper protocol parameter settings per priority message result in an efficient solution for priority based broadcast IVC. Moreover, the proposed protocol is fully compatible with both IEEE 802.11 and IEEE 802.11e standards.